A novel stem-cell population in adult liver with potent hematopoietic-reconstitution activity - Kotton, Darrell N. (The American Society of Hematology, 2005)
A number of recent reports have documented that cells possessing hematopoietic-reconstitution ability can be identified and isolated from a variety of solid organs in the adult animal. In all studies to date, however, purified organ-derived stem cells demonstrate a diminished repopulating capacity relative to that of purified bone marrow–derived hematopoietic stem cells (BM HSCs). It has therefore been unclear whether organ-derived HSCs possess functional properties distinct from those of BM HSCs, or simply have not been purified to a comparable extent. Here we report the identification of a rare subset of cells in adult murine liver that possess potent blood-repopulating potential, approaching that of BM HSCs. The cells, isolated on the basis of dye-efflux activity and CD45 expression (termed CD45(+) liver side population [SP] tip cells), exhibit a surface phenotype similar to that of freshly isolated BM HSCs derived from normal adult animals, but are phenotypically distinct in that they do not express the stem-cell marker c-kit. Single-cell transplantation studies indicate that CD45(+) liver SP tip cells can be generated from BM HSCs, suggesting a relationship between stem-cell populations in the liver and bone marrow compartments. Overall, these studies have important implications for understanding extramedullary hematopoiesis, and may be relevant to current strategies aimed at inducing tolerance to transplanted organs.